Large-scale distributed systems and energy efficiency : a holistic view - Pierson, Jean-Marc (Hoboken, New Jersey : Wiley, 2015)
'This book discusses energy efficiency in large-scale systems. It provides an overview of current energy-reducing technologies and the energy consumption method, addressing topics such as cloud computing, high-performance computing, networks and more. The book begins with an introduction to energy demands in ICT. It then covers topics like green wired/wireless networks, mobile computing, power modeling, green data centers and high-performance computing, resource allocation and energy efficiency in P2P systems'--
Includes bibliographical references and indexes.
Keywords: Data processing service centers -- Energy conservation; Electronic data processing -- Distributed processing -- Energy conservation; Computer networks -- Energy conservation